Alliance Portfolio Configurations and Competitive Action Frequency. (May 2016) - Andrevski, Goce; Brass, Daniel J.; Ferrier, Walter J.
We advance competitive dynamics research by introducing alliance portfolio configuration as an important antecedent of competitive action frequency. We propose and test a model for developing effective alliance portfolio configurations that enhance a firm's ability to discover, conceptualize, and carry out new competitive actions. Our model consists of three overlapping components: (a) opportunity recognition capacity as evidenced by the portfolio attribute of structural holes, (b) opportunity development capacity as indicated by R&D alliance scope, and (c) action execution capacity as exhibited by equity alliances with trusted partners. We hypothesize and find a multiplicative effect of the configuration of all three alliance portfolio attributes on the frequency of competitive actions carried out by 12 large global automobile manufacturing firms with 1, 471 unique partners and 37, 520 alliances formed over a 16-year period (1988 to 2003). The three-way configuration of portfolio attributes was stronger for more complex competitive actions requiring more time, expertise, and resources to develop and execute.